Toxicity of different polycyclic aromatic hydrocarbons (PAHs) to the freshwater planarian Girardia tigrina - Simão, Fátima C. P. (2020)
Freshwater planarians have been gaining relevance as experimental animals for numerous research areas given their interesting features, such as high regeneration potential, shared features with the vertebrates' nervous system or the range of endpoints that can be easily evaluated in response to contaminants. Ecotoxicological research using these animals has been steadily increasing in the past decades, as planarians' potentialities for this research area are being recognized. In this work, we used polycyclic aromatic hydrocarbons (PAHs) as model contaminants and evaluated effects of exposure to phenanthrene, pyrene and benzo[a]pyrene (B[a]P) in planarians. The freshwater planarian Girardia tigrina was chosen and mortality, cephalic regeneration (during and post-exposure), behavioral endpoints and presence of PAHs in tissues, were evaluated. Mortality was only observed in planarians exposed to phenanthrene, with an estimated LC50 of 830 μg L-1. Results indicate that planarian behavioral endpoints were very sensitive in response to sub-lethal concentrations of PAHs, showing a greater sensitivity towards B[a]P and pyrene. Briefly, post-exposure locomotion and post-exposure feeding were significantly impaired by sub-lethal concentrations of all compounds, whereas regeneration of photoreceptors was only significantly delayed in planarians exposed to pyrene. Moreover, levels of PAH-type compounds in planarian tissues followed a concentration-dependent increase, showing uptake of compounds from experimental solutions. The present results highlight the importance of studying alternative and complementary endpoints, such as behavior, not only because these may be able to detect effects at lower levels of contamination, but also due to their ecological relevance. The simplicity of evaluating a wide range of responses to contaminants further demonstrates the utility of freshwater planarians for ecotoxicological research.